Management plans and cash transfers for smallholders: Evidence from Senegal - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (International Food Policy Research Institute, 2017)
Overall, the study shows that large, one-time cash transfers aimed at increasing agricultural investments can significantly impact smallholders’ agricultural production. This differs from previous findings in the literature, which have found more modest impacts of cash transfers on agricultural investments. It is possible that the difference in results may stem from the agricultural training and support that accompanied the cash transfer. However, the study found little evidence that the farm management plan alone can be effective. This finding suggests that for programs aimed at “gradu-ating” smallholder farmers from subsistence production to more high- value, commercial production, cash transfers may be the most critical component for overcoming production constraints.